Lemma 42.67.5. In Situation 42.67.1 let $Y \to X \to S$ be locally of finite type and let $Y' \to X' \to S'$ be the base change by $S' \to S$. Assume $f : Y \to X$ is flat of relative dimension $r$. Then $f' : Y' \to X'$ is flat of relative dimension $r$ and the diagrams

$\vcenter { \xymatrix{ Z_{k + r}(Y) \ar[r]_{g^*} & Z_{k + c + r}(Y') \\ Z_ k(X) \ar[r]^{g^*} \ar[u]^{(f')^*} & Z_{k + c}(X') \ar[u]_{f^*} } } \quad \text{and}\quad \vcenter { \xymatrix{ \mathop{\mathrm{CH}}\nolimits _{k + r}(Y) \ar[r]_{g^*} & \mathop{\mathrm{CH}}\nolimits _{k + c + r}(Y') \\ \mathop{\mathrm{CH}}\nolimits _ k(X) \ar[r]^{g^*} \ar[u]^{(f')^*} & \mathop{\mathrm{CH}}\nolimits _{k + c}(X') \ar[u]_{f^*} } }$

of cycle and chow groups commutes.

Proof. It suffices to show the first diagram commutes. To see this, let $Z \subset X$ be an integral closed subscheme of $\delta$-dimension $k$ and denote $Z' \subset X'$ its base change. By construction we have $g^*[Z] = [Z']_{k + c}$. By Lemma 42.14.4 we have $(f')^*g^*[Z] = [Z' \times _{X'} Y']_{k + c + r}$. Conversely, we have $f^*[Z] = [Z \times _ X Y]_{k + r}$ by Definition 42.14.1. By Lemma 42.67.3 we have $g^*f^*[Z] = [(Z \times _ X Y)']_{k + r + c}$. Since $(Z \times _ X Y)' = Z' \times _{X'} Y'$ by associativity of fibre product we conclude. $\square$

In your comment you can use Markdown and LaTeX style mathematics (enclose it like $\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).